Surveillance and Surveillance Detection : a cia insider's guide - Kiriakou, John C. (New York: Skyhorse Publishing, 2022)
"From former CIA counterterrorism officer John C. Kiriakou, Surveillance and Surveillance Detection: A CIA Insider's Guide takes you through the CIA's surveillance and surveillance detection program. It will teach you to apply CIA surveillance techniques to your own everyday life. You'll learn how to stay safe, to ensure your privacy, and to keep the honest people honest--the CIA way"
Keywords: Surveillance Detection; Intelligence Service